Wage Differentials and Mobility in the Urban Labor Market: A Panel Data Analysis for Mexico - Xiaodong Gong; Arthur van Soest (Institute for the Study of Labor (IZA), 2001)
We analyze wage differentials mobility between the formal and informal sector in urban Mexico, using panel data on five quarters drawn from Mexico?s Urban Employment Survey. We develop a dynamic random effects panel data model. It consists of two separate wage equations for the two sectors and a multinomial logit part explaining the labor market state, in which wages are included as explanatory variables. The model is estimated using simulated maximum likelihood. The estimates show that wage differentials increase with education level. The probability of formal sector employment strongly increases with the wage differential. Simulated transition probabilities show that for male workers, the choice between formal and informal sector is driven by wage differentials and unobserved heterogeneity, while true state dependence is much less important. For women, nonparticipation is the most common labour market state, and true state dependence plays a much larger role.
Keywords: J31; R23; C33; J23; 330; Wage differentials; informal sector; mobility; panel data; Mexico; Lohnstruktur; Informeller Sektor; Städtischer Arbeitsmarkt; Arbeitsmobilität; Schätzung; Mexiko